Effect of Dicamba and Adjuvant Combination on Parthenium Control, Fodder Yield and Yield Components of Forage Sorghum (Sorghum bicolor) - ASIF,M. (2019)
ABSTRACT: Parthenium is an important weed which poses severe threats to yield and quality of sorghum and many other summer season crops, worldwide. As in other field crops, parthenium also reduces yield and quality of forage plants in forage crops so it should be controlled in forage and fodder crops. Parthenium control efficacy of five herbicide treatments (including dicamba at 304.5 g a.i. ha-1 (full rate) alone, dicamba at full rate + 1% ammonium sulphate, dicamba at full rate + 2% ammonium sulphate, dicamba at 75% rate + 1% ammonium sulphate and dicamba at 75% rate + 2% ammonium sulphate) was tested in field trials for two consecutive years (2013 and 2014). One manual hoeing three weeks after crop emergence was also performed as a treatment and weedy check was kept as control. Application of the full rate of dicamba with 2% ammonium sulphate showed the lowest parthenium dry weight (16.5 g m-2 and 23.5 g m-2) and NPK uptake that seem to be due to the highest parthenium control efficiency of 79.6% and 73.8% during 2013 and 2014, respectively. This weed management strategy also gave maximum values of yield components of forage sorghum, including plant height (261 and 254 cm), stem diameter (0.97 and 0.84 cm), leaf area per plant (3,072 and 3,041 cm2), fresh fodder yield (63.4 and 60.9 t ha-1) and dry matter yield (17.4 and 15.8 t ha-1) in 2013 and 2014, respectively. Highest net return and marginal rate of return (346 and 356% in 2013 and 2014, respectively) were also found when the full rate of dicamba with 2% ammonium sulphate was applied. In conclusion, tank-mixed application of dicamba at 304.5 g a.i. ha-1 with 2% of ammonium sulphate proved to be better for efficient control of parthenium weed in forage sorghum.